Virtual Reality Assessment of Classroom – Related Attention: An Ecologically Relevant Approach to Evaluating the Effectiveness of Working Memory Training - Coleman, Benjamin; Marion, Sarah; Rizzo, Albert; Turnbull, Janiece; Nolty, Anne (Frontiers in Psychology, 2019)
Computerized cognitive interventions to improve working memory also purport to improve ADHD-related inattention and off task behavior. Such interventions have been shown to improve working memory, executive functioning, and fluid reasoning on standardized neuropsychological measures. However, debate continues as to whether such programs lead to improvement on ecologically relevant outcomes, such as classroom behavior. This study sought to evaluate the effectiveness of working memory training on real-world attention performance. Participants included 15 children, aged 6 to 15, identified as having learning and attention problems. Both before and after completing five weeks of Cogmed Working Memory Training, each child was assessed via the Virtual Classroom Continuous Performance Task, a validated measure of sustained attention set within a virtual environment. Several key areas of attention performance were observed to improve, including omission errors, reaction time, reaction time variability, and hit variability. Results suggest that working memory training led to substantial improvements in sustained attention in a real-life scenario of classroom learning. Moreover, the use of psychometrically-validated virtual reality measurement provides incremental validity beyond that of teacher or parent report of behavior. Observing such improvements on ecologically relevant measures of attention adds to the discussion around computerized working memory training as a viable option to treat attention disorders and serves to inform consumer awareness of such products and their claims.